Analysis of the Effect of Service Communication Quality of UP3 PT PLN (Persero) Ampenan Area Toward Postpaid Customer Satisfaction in Mataram City - Ahmad Lutfi Hakki; Diyah Indiyati; Agus Purbathin Hadi (JCommsci - Journal Of Media and Communication Science, 2019)
This study aims to examine the effect of service communication quality of UP3 PT PLN (Persero) Ampenan Area with indicators of Clear, Responsive, Polite, Solutive, Ready, Empathy, Gesture, Listen, and Honest, on postpaid customer satisfaction in Mataram City with indicators of Needs and Expectations . The theories used in this study are Stimulus-Response communication theory, Social Penetration theory, and Social Exchange theory. This research is a correlational quantitative study. Data collection is done using survey techniques and interviews. The population of this study is that all residents of Mataram City use postpaid electricity, while the respondents in this study amounted to 100 people who were selected using Purposive Sampling and Non probability Sampling techniques. Data analysis of this study was carried out by categorizing data into high, medium, low using Microsoft Excel programs, then tested the validity, reliability test, Spearman rank correlation test and regression test using the SPSS program. The results of this study indicate that there is a strong or significant relationship between the quality of service communication on customer satisfaction, and customer satisfaction by 37.5% influenced by the quality of service communication. In addition, the type of relationship formed is a unidirectional relationship, meaning that if the quality of service communication increases, it will increase customer satisfaction. Keywords: Service Communication; PT PLN (Persero) Ampenan; Postpaid Customer Satisfaction